Insights into the Roles of Lipoteichoic Acids and MprF in Bacillus subtilis - Aurélie Guyet; Amirah Alofi; Richard A. Daniel (mBio, 2023)
ABSTRACT Gram-positive bacterial cells are protected from the environment by a cell envelope that is comprised of a thick layer of peptidoglycan that maintains cell shape and teichoic acid polymers whose biological function remains unclear. In Bacillus subtilis, the loss of all class A penicillin-binding proteins (aPBPs), which function in peptidoglycan synthesis, is conditionally lethal. Here, we show that this lethality is associated with an alteration of lipoteichoic acids (LTAs) and the accumulation of the major autolysin LytE in the cell wall. Our analysis provides further evidence that the length and abundance of LTAs act to regulate the cellular level and activity of autolytic enzymes, specifically LytE. Importantly, we identify a novel function for the aminoacyl-phosphatidylglycerol synthase MprF in the modulation of LTA biosynthesis in both B. subtilis and Staphylococcus aureus. This finding has implications for our understanding of antimicrobial resistance (particularly to daptomycin) in clinically relevant bacteria and the involvement of MprF in the virulence of pathogens such as methicillin-resistant S. aureus (MRSA). IMPORTANCE In Gram-positive bacteria such as Bacillus subtilis and Staphylococcus aureus, the cell envelope is a structure that protects the cells from the environment but is also dynamic in that it must be modified in a controlled way to allow cell growth. In this study, we show that lipoteichoic acids (LTAs), which are anionic polymers attached to the membrane, have a direct role in modulating the cellular abundance of cell wall-degrading enzymes. We also find that the apparent length of the LTA is modulated by the activity of the enzyme MprF, previously implicated in modifications of the cell membrane leading to resistance to antimicrobial peptides. These findings are important contributions to our understanding of how bacteria balance cell wall synthesis and degradation to permit controlled growth and division. These results also have implications for the interpretation of antibiotic resistance, particularly for the clinical treatment of MRSA infections.